Studies on the potential for treatment with short wave ultraviolet light (UV-C) to reduce postharvest diseases in banana fruit crown (Musa sp., group AAA, subgroup Cavendish) - Uribe Palacio, Simón (2022)
Postharvest use of fungicides is getting more restricted, highlighting the necessity to investigate alternative treatments. The objective of this work was to evaluate the effect of UV-C treatments on Crown Rot and fruit quality in banana fruit. Preliminary tests were conducted on the crown of banana fruit applying UV-C doses at 0, 0.4, 0.6, 1.0, or 1.3 kJ m-2 while covering the rest of the fruit with protective material. The UV-C treatment at 1.3 kJ m-2 showed similar incidence of Crown Rot and Mold compared to the commercial control (fungicide). UV-C applied directly on banana fruit without protection, caused browning and peel damage at doses greater than 0.4 kJ m-2. In a following experiment, UV-C doses at 1.0 and 1.3 kJ m-2 were applied on the crown while protecting the rest of the fruit to validate their efficiency in reducing Crown Rot and Mold. In the last experiment, before applying UV-C at 1.0 and 1.3 kJ m-2, banana fruit were inoculated with a solution containing Colletotrichum musae, Fusarium semitectum and F. proliferatum, which are the pathogen agents causing postharvest Crown Rot. Fruit quality was not affected by UV-C treatments including color (b*) and electrolyte leakage (%) compared to commercial treatment. Results suggest that application of UV-C treatments at 1.0 or 1.3 kJ m-2 on banana crowns after harvest could be an alternative to control postharvest Crown Rot and Mold.